- PEMIDANAAN TERHADAP TINDAK PIDANA PERCOBAAN PENCURIAN YANG DIPUTUS DENGAN KETENTUAN PASAL 362 KUHP (STUDI KASUS PUTUSAN PENGADILAN NEGERI BINJAI NOMOR 406/PID.B/2021/PN BNJ) : - - Ammar Farras Fauzan; Setiyono (Reformasi Hukum Trisakti, 2023)
Not just the perpetrator's purpose, but also the availability of the opportunity to commit the attempted steal, are factors that affect its incidence. As in this instance where the perpetrator's activities in judgment number. 406/Pid.B/2021/PN Bnj were judged under Article 362 of the Criminal Code relating common theft despite the defendant Edy Susanto's attempted criminal act. The key issue is whether the stealing crime has been fully formed in accordance with Article 362 of the Criminal Code's regulations. Data collection was done through literature study in this normative study, which used the kind and/or nature of analytical descriptive research as well as the usage and/or utilization of secondary data. The perpetrator's actions would be more appropriate if they were decided in accordance with Article 362 and Article 53 of the Criminal Code regarding attempted theft because the perpetrator's actions did not satisfy the elements in Article 362 of the Criminal Code regarding theft because they were not completed. Edy Susanto received a sentence that was a penalty for an attempted crime, with the maximum main term for the offence being lowered by one-third.